Effect of Radial Spacing on the Growth and Yield of Maize under Olla Irrigation (Global Journal of Science Frontier Research, 2017)
This research was carried out in Federal College of Forestry Jos, during the 2015/2016 cropping season, to determine the Effect of radial spacing on growth and yield of Maize (Zea mays L.) under Olla irrigation. The experiment consisted of four (4) treatment each replicated three (3) times in randomized complete block design (RCBD) .The parameters assessed were plant height, stem diameter, leaf count and grain yield. The spacing of 25x10cm (T 1 ) gave the highest plant height followed by 25x20cm (T 2 ) and 25x30cm (T 3 ), while 25x40cm (T 4 ) had the lowest. The spacing distance of 25x10cm recorded the highest stem diameter of 7.50cm while 25x40cm had the least value of 5.77cm.The same pattern was observed for the leaf count with highest value of 8.33cm for treatment one (T 1 ), while T 4 recorded the lowest value of 15.67cm respectively. The Grain yield ranged from 2.20-12.22t/ha for treatment considered recorded under Treatment. The analysis of variance revealed significant difference (p0.05) was recorded for leaf count. When the radial spacing from the Olla Pot was increased from 10 to 20, 30 and 40cm; the corresponding yield reduction values were 33, 58 and 82%.
Keywords: Olla irrigation; radial spacing; grain yield; maize